Biological Removal of Dyes from Wastewater: A Review of Its Efficiency and Advances - Kuok Ho Daniel Tang; Noura M. Darwish; Abdullah M Alkahtani; Mohamed Ragab AbdelGawwad; Peter Karácsony (Tropical Aquatic and Soil Pollution, 2022)
Biological removal of dyes has been advocated due to its simplicity, cost-effectiveness, and low operational requirements in comparison to physicochemical methods of treating dye effluents. This paper aims to compare the efficiency of biological removal of dyes using bacteria, algae, and fungi, including yeasts, besides presenting the recent advances in the field. This paper reviewed scholarly articles published mainly between 2010 and 2021. It found bacteria could degrade a myriad of dyes. Different bacteria could degrade the same dye with different efficiencies. Similarly, one bacterial species could degrade multiple dyes with varying efficiencies. Though regarded as having a faster rate of dye biodegradation than fungi, this review finds bacteria to have comparable performance to fungi in decolorizing dyes, and it is worth mentioning that a few yeast species were reported to have very high efficiency in decolorizing dyes. Mixed bacteria or bacteria-fungus cultures were generally found to have better dye-decolorizing efficiency than pure cultures. Algae have relatively lower efficiency than bacteria and fungi in decolorizing dyes and might require longer contact time. New advances such as genetic engineering as well as immobilization of microorganisms and enzymes could improve the efficiency of dye biodegradation. Nonetheless, before biological removal of dyes can be feasibly applied, there are limitations that need to be overcome. Major limitations include the inconsistent performance of various organisms in decolorizing dyes; the complexity of optimization; inability to completely decolorize dyes; potential formation of toxic by-products upon decolorization of dyes; safety concerns of immobilization materials; and cost and technical feasibility of biological removal of dyes. This review has the significance of highlighting the important bottlenecks of the current biological dye removal technology, which could pave the way for breakthroughs in this domain of research.